Sanitary conditions of the Goliath grouper Epinephelus itajara in captivity on estuarine environment: case report - Paixão,P.E.G. (2020)
ABSTRACT This study aimed to report the sanitary conditions through the hematological analysis of grouper E. itajara reared in captivity on estuarine conditions. Seven Goliath groupers (1,881.5±1,246.03g) were captured and kept in two tanks located on estuary. After 20 days, fish were collected for morphologic and hemato-physiologic evaluation. Two fish had clinical signs such as hemorrhagic spots and loss of scale due to agonistic behavior. Blood samples were collected, and the hematological parameters (biochemical, erythrogram and leukogram) were determined. Blood cells were characterized by their size, color and shape. Univariate statistic and principal components analysis were used to identify a hematological standard between fish with or without clinical signs. Four leukocyte types were found: lymphocyte, monocyte, neutrophil and basophil. Regardless of the clinical signs the cell morphology did not present any difference among the fish. However, there is a significant correlation between erythrocyte and lactate on fish with clinical signs. Thus, agonistics encountered among the fish is a stressing factor in captivity conditions making it necessary to have adequate management related to the size of fish and stocking density.